Explication Des Evangiles des Dimanches (Imprimerie de La Societe des Missions Etrangeres, 1874)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm

Exposition du Dogme Catholique (P. Lethielleux, Libraire-Editeur, 1874)
Stamp
Keywords: 1.Conservation 保護; 6.Yellowing 變黃; Fair

Les Auteurs Grecs (Librairie Hachette Et C, 1874)
Keywords: Condition: Fair; Hard Cover; Literature

Oeuvres Pastorales de S. E. le Cardinal Jaochim Pecci (Desclee, De Brouwer & Cie, 1874)
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

S. Anselmi Catuariensis Archiepiscopi de Divinitatis Essentia (apud David Nutt, 1874)
Stamp
Keywords: 1.Conservation 保護; 10.Cover Damage; 2.Damage; 6.Yellowing 變黃

S. Aurelii Augustini, Hipponensis Episcopi, de Ecclesia Christi (apud Boniarid- Pogliani, 1874)
Stamp
Keywords: 1.Conservation 保護; 10.Cover Damage; 2.Damage; 6.Yellowing 變黃

Manual de Direito Ecclesiastico - Antonio Xavier de Sousa Monteiro (Livraria poetugueza e extrangeira, 1874)
Stemp of St. Joseph Seminary
Keywords: Poor

Portugal, antigo e moderno : diccionario geographico, estatistico, chorographico, heraldico, archeologico, historico, biographico e etymologico de todas as cidades, villas e freguezias de Portugal - Augusto Soares d'Azevedo Barhosa de Pinho Leal (Livraria Editora de Mattos Maoreira & Companhia, 1874)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; 22.signature; Condition: Fair; Hard Cover; History

Oracao Gratulatoria que em presenca de suas magestades e alterzas - Figueira, Francisco da Silva (Imprensa de Jaoquim Germano de Sousa Neves, 1874)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 2.Damage

Diccionario dos synonymos poetico e de epithetos da lingua portugueza - Fonseca Lessa, José Antonio da; Roquete, J. I. (1874)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; 22.stamp; Condition: Fair; Dictionaries; Hard Cover; languages

Geometria Elementar Theorica E Practica - Francisco de Castro Freire; Rodrigo Ribeiro de Sousa Pinto (Livraria Portugueza E Estrangeira, 1874)
Keywords: 10.Cover Damage; 2.Damage; Condition: Fair

Les Livres Saints Venges - Glaire, J. B (A. Jouby et Roger, Libraires- Editeurs, 1874)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage

Les Livres Saints Venges - Glaire, J. B (A. Jouby et Roger, Libraires- Editeurs, 1874)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage

Les Livres Saints Venges ou La Verite Historique et Divine - Glaire, J. B (Maison Méquignon Junior, 1874)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 15.Stain 污漬; 18.Bookworm; 2.Damage

Theologia Dogmatie Moral-Explicacao Historica do Catecismo - Guillois, Abbade Ambrosio (Libraria Internacional, 1874)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

Explicação historica dogmatica, moral, liturgica e canonica do catecismo com a resposta ás objecções extrahidas das sciencias contra a religião - Guillois, Ambrosio (Ernesto Chardron, 1874)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Condition: Fair; Hard Cover; History; Religion

Explicação historica dogmatica, moral, liturgica e canonica do catecismo com a resposta ás objecções extrahidas das sciencias contra a religião - Guillois, Ambrosio (Ernesto Chardron, 1874)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Condition: Fair; Hard Cover; History; Religion

Explicação historica dogmatica, moral, liturgica e canonica do catecismo com a resposta ás objecções extrahidas das sciencias contra a religião - Guillois, Ambrosio (Ernesto Chardron, 1874)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Condition: Fair; Hard Cover; History; Religion

Explicação historica dogmatica, moral, liturgica e canonica do catecismo com a resposta ás objecções extrahidas das sciencias contra a religião - Guillois, Ambrosio (Ernesto Chardron, 1874)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Condition: Fair; Hard Cover; History; Religion

Explicação historica dogmatica, moral, liturgica e canonica do catecismo com a resposta ás objecções extrahidas das sciencias contra a religião - Guillois, Ambrosio (Ernesto Chardron, 1874)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Condition: Fair; Hard Cover; History; Religion

Explicação historica dogmatica, moral, liturgica e canonica do catecismo com a resposta ás objecções extrahidas das sciencias contra a religião - Guillois, Ambrosio (Ernesto Chardron, 1874)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Condition: Fair; Hard Cover; History; Religion

Explicação historica dogmatica, moral, liturgica e canonica do catecismo com a resposta ás objecções extrahidas das sciencias contra a religião - Guillois, Ambrosio (Ernesto Chardron, 1874)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Condition: Fair; Hard Cover; History; Religion

Explicação historica dogmatica, moral, liturgica e canonica do catecismo com a resposta ás objecções extrahidas das sciencias contra a religião - Guillois, Ambrosio (Ernesto Chardron, 1874)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Condition: Fair; Hard Cover; History; Religion

Explicação historica dogmatica, moral, liturgica e canonica do catecismo com a resposta ás objecções extrahidas das sciencias contra a religião - Guillois, Ambrosio (Ernesto Chardron, 1874)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Condition: Fair; Hard Cover; History; Religion

Diccionario dos Synonymos da Lingua Portugueza - J I Roquete; Jose da Fonseca (Aillaud, Guillaro e Eia, 1874)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Condition: Fair; Dictionaries

Esboco De Philosophia Analytica - J. L. Artt Milner (Libraria Editora De Mottos Moreira, 1874)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Condition: Fair; Philosophy

Compendio De Geographia - Joao Felix Pereira (62- Rua do Cruifixo-66, 1874)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Condition: Fair; Hard Cover

Chorographia moderna do reino de Portugal - João Maria Baptista (Typographia da Academia Real das Sciencias, 1874)
Keywords: 10.Cover Damage; 2.Damage; Condition: Fair; History

Epistolae Selectae - Magni, S. Leonis (apud David Nutt, 1874)
Keywords: 1.Conservation 保護; 10.Cover Damage; 2.Damage

Epistolae Selectae - Magni, S. Leonis (apud David Nutt, 1874)
Keywords: 1.Conservation 保護; 10.Cover Damage; 2.Damage

As Tres Romas - Monsenhor Gaume (EM Casa De A . R. Cruz Coutinho., 1874)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; 22.signature; 22.stamp; Condition: Poor; Hard Cover

No Presbyterio E No Templo - Padre Senna Freitas (Livraria Internacional, 1874)
Stemp of St. Joseph Seminary
Keywords: Fair

No Presbyterio E No Templo - Padre Senna Freitas (Livraria Internacional, 1874)
Stemp of St. Joseph Seminary
Keywords: Fair

historia sagrada - ROQUETE, J.-I. (EM CASA DE VA J.-P.AILLAUD ,GUILLARD E CA, 1874)
Keywords: History

Historica Sagrada Do Antigo E Novo Testamento - ROQUETE, J.-I. (EM CASA DE VA J.-P.AILLAUD ,GUILLARD E CA, 1874)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; 22.signature; Condition: Fair; Hard Cover; History

Historia da litteratura Camoes - Theophilo Braga (Imprensa portugueza, 1874)
Keywords: 18.Bookworm; 2.Damage; Condition: Fair; Hard Cover; History

Do Uso Frequente e Diligente da Confissao e Communhao - Vitale, Thomaz (Imprensa Litteraria, 1874)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm (Only Cover)